Prevalence of and Risk Factors for Pterygia in a Rural Northern Chinese Population. (December 2014) - Li, Zhijian; Wu, Shubin; Mai, Jieying; Xu, Keke; Sun, Ying; Song, Zhen; Jin, Di; Wang, Haijing; Liu, Ping
Abstract Purpose: To determine the prevalence of and associated risk factors for pterygia development in a high-latitude-dwelling Northern Chinese population. Methods: A prospective population-based survey was conducted between November 2008 and July 2009. A stratified, clustered, randomized sampling procedure was used to select 8445 subjects, aged ≥18 years, all with diagnosed, graded pterygia. Risk factors associated with the occurrence of pterygia were evaluated according to logistic regression models. Results: A total of 8445 residents (aged 18–94 years) from the Heilongjiang Province, China, participated in the study. Of these, 208 (2.5%) had at least one diagnosed pterygium. The prevalence of bilateral pterygia was 1.2% (95% confidence interval, CI, 1.0–1.4%). According to multivariable analysis, pterygia were significantly more likely to occur in persons aged 70–94 years than in those aged 18–39 years (odds ratio, OR, 29.0, 95% CI 13.6–61.6, p < 0.01). Pterygia were significantly associated with male sex (OR 1.9, 95% CI 1.4–2.6, p < 0.01) and outdoor work (OR 1.8, 95% CI 1.2-2.6, p < 0.01). Multivariable analysis indicated that pterygia were not associated with smoking status (OR 1.0, 95% CI 0.8–1.4) or alcohol intake (OR 1.0, 95% CI 0.7–1.4, p > 0.05). Conclusions: This study details the occurrence of and risk factors for pterygia in a Chinese population residing in a rural, high-latitude, cold-climate area of Northern China. The primary risk factors for pterygia were age, male sex, and outdoor work.